2012
DOI: 10.1590/s0100-879x2012007500143
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate for the treatment of osteoporosis secondary to chronic cholestatic liver disease in Wistar rats

Abstract: Osteoporosis is a major complication of chronic cholestatic liver disease (CCLD). We evaluated the efficacy of using disodium pamidronate (1.0 mg/kg body weight) for the prevention (Pr) or treatment (Tr) of cholestasis-induced osteoporosis in male Wistar rats: sham-operated (Sham = 12); bile duct-ligated (Bi = 15); bile duct-ligated animals previously treated with pamidronate before and 1 month after surgery (Pr = 9); bile duct-ligated animals treated with pamidronate 1 month after surgery (Tr = 9). Rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Corroborating previous studies that showed the impact of chronic hepatic disorder on the skeleton, the present study contributes to advancements in this line of investigation. Based on the previous experience of our group in the study of bone disturbances in cholestasis (clinical and experimental) 10 - 12 , 19 , we observed conspicuous differences in bone remodeling using an experimental model of cirrhosis. While the predominant bone impairment seems to be low osteoblastic activity in cholestasis, in hepatocellular disease, increased osteoclastic action appears to be the major mechanism of bone loss.…”
Section: Discussionmentioning
confidence: 88%
“…Corroborating previous studies that showed the impact of chronic hepatic disorder on the skeleton, the present study contributes to advancements in this line of investigation. Based on the previous experience of our group in the study of bone disturbances in cholestasis (clinical and experimental) 10 - 12 , 19 , we observed conspicuous differences in bone remodeling using an experimental model of cirrhosis. While the predominant bone impairment seems to be low osteoblastic activity in cholestasis, in hepatocellular disease, increased osteoclastic action appears to be the major mechanism of bone loss.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, NTX injection did not lead to a statistically significant increase in these parameters. Nevertheless, additional studies have shown notable reductions in one or a combination of these indices in rats undergoing BDL-induced cholestasis 41 – 43 . Decreased levels of these parameters may indicate the successful execution of our BDL surgery.…”
Section: Discussionmentioning
confidence: 99%